Strategi Sukses Manajemen Kreativitas dan Inovasi dalam Pengembangan Pengembangan Bisnis Ice Cream Pink Chiling - Manik, Gia Cinta Saria; Pohan, Malvira; Simatupung, Simeon Adrian; Lubis, Putri Kemala Dewi (MES Bogor, 2024)
This research discusses the management of creativity and innovation in the ice cream business in Indonesia, with a focus on the Pink Chilling business case study. Globalization and technological advances have encouraged companies to continue to innovate in order to survive and develop in intense competition. This research uses a qualitative approach with data collection methods through interviews and literature analysis. The research results show that Pink Chilling is an ice cream business founded in April 2023 by the Agustina family. By using innovation in product prices, menu variations and creative services, Pink Chilling has succeeded in attracting customer interest and increasing market share. The implementation of creative management policies, systematic supervision, and innovative sales strategies have helped Pink Chilling create a work environment that supports creativity and innovation, as well as increasing customer satisfaction and business growth. This research concludes that creativity and innovation management play an important role in the success of the Pink Chilling ice cream business, as well as providing insight into the importance of creative strategies in facing intensive business competition.